Evaluación de métodos de cultivo de macroalga gracilariopsis sjoestedtii en campo en la zona sur de la isla Jambelí El Oro - Jaya Lusuriaga, Miguel Ángel (2014)
The Cultivation Methods for Macroalgae (Gracilariopsis sjoestedtii) evaluation in the southern fieldwork of Jambelí Island was carried out in the months of October, November and December 2010. Macroalgal (Gracilariopsis sjoestedtii) implants were taken from a main distribution channel of water for “El Cisne” shrimp farm, in "La Calavera" Jambelí’s archipelago, owned by the distinguished Dr. Benigno Granda, with his consent and logistical support. The implants obtained were sufficient resources to develop the two culture methods. The distance from where Macroalgae (Gracilariopsis sjoestedtii) implants were taken, regarding to place of research was conducted, it was about 200 meters. The removal of the implants at the workplace is carried out at night to avoid the least possible damage to the room temperature implants. Implants were of excellent quality: showed no biotic or abiotic adhesions, weight and size were taken for each method for implantation. Prior to removal the implants, the method "sandbags" method proceed, taking sand from the place and the natural sterilizing UV radiation, mixture of sand and fertilizer is then placed in plastic bags of 12 cm wide by 40 cm long, tied and anchored respectively to the ends. In each plastic sleeve are placed three implants of Macroalgae (Gracilariopsis sjoestedtii) weighing approximately 75 g to a separation of 15 cm between the implants. Prior to placement, biometric parameters are taken weight and size every two weeks, while the abiotic parameters are taken daily. Parallel lines were constructed by plastic ropes of 5 mm think, stakes of 40 cm long that served as supports for tuning the plastic rope are taken. To this string is placed implants from a size of 10 cm and greater mass of 50 g and less than 90 g. Implants were hanging in the plastic rope with a spacing of 10 cm between implants and 15 cm between ropes. The first solid fertilizer based on urea and DAP is then placed in four proportional points of parallel lines. The fertilizer dose was 80 g of urea and 20 g of DAP, placed in cotton bags, these cotton bags were buried at 10 cm, the number of bags of fertilizer were four and the amount of the mixture was 40 g. Weight and size were taken to implants every two weeks for two months; at the third month, implants began to deteriorate until it disappears completely, the main reason: temperature changed in December.